Travel decision making through blogs and vlogs: An empirical investigation on how user-generated content influences destination image - Jog, Deepti R.; Alcasoas, Nelissa Andrea (Turyzm/Tourism, 2023)
Tourist decision-making is based on the information available before visiting a destination. Although marketing content has a role to play, user-generated content (UGC) has gained momentum in recent years. This study considering the role of travel blogs and vlogs created by the user, aims to comprehend the role of these information sources in the decision-making of their consumers. The present research investigates the preference of travelers for UGC and its role in travel decision-making over other marketing information generated by destination marketing organisations (DMOs). The study is based on responses from 220 Indian tourists via an online web-based survey conducted using a structured questionnaire and applying multi-stage sampling. The study findings reveal a strengthened preference for blogs and vlogs among travelers compared to traditional DMO marketing content. The study provides implications for industry players that can help engage their visitors in UGC creation and dissemination for better marketing by suggesting suitable strategies for tourism.